FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Angelica Gisella; Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2026)
The purpose of this study is to obtain empirical evidence regarding the factors that influence firm value which includes return on asset, cash holding, and managerial ownership as moderating variable. The research was conducted towards 36 manufacturing companies in consumer goods variable, miscellaneous industry sector, and basic and chemical industry sector in 2019-2021. This study was conducted with a sample of 106 data with purposive sampling technique with multiple regression analysis. Data processing in this studymuses the Eviews 12 program. The result of this study shows that return on asset has positive effect on firm value, cash holding has negative effect on firm value, and managerial ownership has no negative effect on firm value. In addiction, managerial ownership cannot moderate the effect of return on asset on firm value. The implication of this study is expected to provide benefits for the development of knowledge such as contributions that can be useful in economics and business studies, especially accounting which are generally related to company value.